Comparative observation of common tracers in sentinel lymph node biopsy of breast cancer and a study on simplifying its surgical procedure - Sun, Shuo; Bai, Jiming; Wang, Xiang (Frontiers in Surgery, 2023)
Background Many breast cancer patients have avoided axillary lymph node dissection after sentinel lymph node biopsy (SLNB). During the SLNB operation, the color of lymphatic vessels is sometimes poor and so finding them is difficult. This study observed the tracing effects of three tracer combinations and also reported our experience in simplifying the SLNB program. Methods In total, 123 breast cancer patients whose TNM stage was cT1–2N0M0 were retrospectively studied. According to the tracer used, the patients were divided into the carbon nanoparticle (CNP) group (38 cases), CNP combined with methylene blue (CNP + MB) group (41 cases), and indocyanine green combined with MB (ICG + MB) group (44 cases). All 123 breast cancer cases were also classified into the non-tracking group (53 cases) and tracking group (70 cases) according to the SLNB operation process. The non-tracking group looked for the stained sentinel lymph nodes directly, while the tracking group looked for the stained lymph nodes along the lymphatic vessels. Results The SLN identification rates in the CNP, CNP + MB, and ICG + MB groups were 97.4%, 97.6%, and 95.5% respectively (P > 0.05). The average number of SLNs detected was 4.92 ± 2.06, 5.12 ± 2.18, and 4.57 ± 1.90, respectively (P > 0.05). The ideal display rates of lymphatic vessels in the three groups were 86.8%, 87.8%, and 93.2%, respectively (P > 0.05). The SLN identification rates in the non-tracking and tracking groups were 96.2% and 97.1%, respectively (P > 0.05). The average number of SLNs detected were 5.73 ± 1.76 and 5.70 ± 1.93, respectively (P > 0.05), and the average operation time was 16.47 ± 5.78 and 27.53 ± 7.75 min, respectively (P < 0.05). Conclusion This is the first study to observe the application effect of CNP combined with MB and ICG combined with MB tracers in SLNB of breast cancer patients. No significant difference was observed among the patients in SLN identification and lymphatic vessel display. Omitting the step of searching for lymphatic vessels in SLNB surgery does not reduce the surgical effect, but the reduced operating steps can reduce the surgical time and theoretically reduce postoperative complications.